GW24-e2985 Stem cell therapy: a meta-analysis of randomised Controlled trials in chronic heart failure. (1st October 2013) - Rui, Yan; Yan, Rui; Zhang, Ming; Lin, Lin; Shan, Hu; He, Le; Wei, Jin
Abstract : Objectives: To evaluate whether stem cell therapy in chronic heart failure could improve cardiac function and clinical outcomes, then to realise the incidence of adverse events in the procedure. Methods: A systematic literature search was conducted to identify randomised controlled trials of stem cell therapy for chronic heart failure in PubMed and Cochrane Library by independent two authors between 2001 and Dec. 2012. Reports of trials were sought that compared stem cell with optimal treatment for chronic heart failure in adults. Then according to the Cochrane Handbook for systematic reviews, we estimate the qulity of the randomised controlled trials and collect the useful information. At last, we choose the variable and process data with RevMan 5.0. Results: 12 trials with data for 431 patients were identified by the literature search. The aetiology of chronic heart failure in patients were ischaemic cardiomyopathy or non-ischaemic dilated cardiomyopathy. Stem cell therapy could significantly improve the left ventricular ejection fraction compared with control treatment in chronic heart failure (weighted mean difference (WMD) 6.09, 95%CI from 3.03 to 8.78, P < 0.0001). At the same time, with stem cell therapy, the cardiac fuction (NYHA) was improved further (WMD -0.77, 95%CI from -1.28 to 0.25, P = 0.003). However, stem cell therapy could not significantly reduce the left ventricular end-diastolic volume (WMD -2.97, 95%CI from -17.88 to 11.93, P = 0.70) and end-systolic volume (WMD -2.97, 95%CI from -17.88 to 11.93, P = 0.33). Besides stem cell therapy did not show a significant protective effect for worsen heart failure (RR 0.49, 95%CI from 0.10 to 2.30, P = 0.37) and mortality (RR 0.77, 95%CI from 0.42 to 1.39, P = 0.38). Meanwhile, stem cell therapy was not associated with the significant increase of ventricular arrhythmia (RR 1.05, 95%CI from 0.56 to 1.97, P = 0.88). Conclusions: Stem cell might be a more effective strategy for chronic heart failure treatment. It can bring some cardiac protection, but according to the existing data, stem cell therapy did not show the superiority for prognosis. More studies, especially larger long-term follow-up RCTs, are needed to clarify the effect and safety of stem cell in chronic heart failure.